Workers Leaving the Studio: Looking Away from Socialist Realism - van Gerven Oei, Vincent W.J; van Gerven Oei, Vincent W.J; Gjikola, Genti (punctum books, 2015)
Workers Leaving the Studio. Looking Away from Socialist Realism. catalogs the exhibition "Workers leaving the studio. Looking away from socialist realism.," curated by Mihnea Mircan in the National Gallery of Arts in Tirana, Albania in 2015. According to Mircan, "The [...] exhibition reflects on another projection machine, whose history and consequences, unlike cinema, are circumscribed by national boundaries, specific histories, and ideological configurations. The regime of production and representation of socialist realism radicalizes the violence that the creation of a new image does to its subject: it intensifies the fraught relation between refashioned representation and that which is represented. Its insistence on a particular, projective notion of reality is commensurate with the coercion of daily - cultural, social, emotional - life into a grid whose perspective lines and vanishing points carry heavy ideological charges. It enforces what it represents onto that which it represents, so that representation would replace reality." Apart from a full documentation of the exhibition by photographer Marco Mazzi, the catalogue also features theoretical and art-historical contributions, both in English and in Albanian, on socialist realist art as developed in Albania under the communist regime, as well as texts highlighting contemporary attempts to display political realities through progressive artistic practices. Artists include: Santiago Sierra, Jonas Staal, Ciprian Mureşan, Irwin, Sarah Vanagt, and Armando Lulaj, with scholarly contributions by